Potentiality of Quantitative and Corpus Analysis to Literary Studies – Toward Methodology (The Analysis of Thematic Fields) - Změlík, Richard (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2016)
The first part of presented study is focused on quantitative and corpus analysis of the first three collections of short stories by the Czech prose writer Jan Čep. Using the definition of so-called thematic field we try to demonstrate how this methodology can be used in the context of literary theory. The study is intended mainly to present the possibilities that contemporary quantitative and corpus analysis offer to the theory of literature. Both disciplines have in fact so far developed without noticeable mutual contacts. Special model of Jan Čep authorial corpus and its analysis should prove potentiality of these primarily linguistic methods also in the theory of literature.
Keywords: Jan Čep; thematic concentration of a text; quantitative and corpus linguistics and theory of literature; model of Jan Čep authorial vocabulary